2003
DOI: 10.1101/gad.1072303
|View full text |Cite
|
Sign up to set email alerts
|

The β-globinlocus control region (LCR) functions primarily by enhancing the transition from transcription initiation to elongation

Abstract: To investigate the molecular basis of ␤-globin gene activation, we analyzed factor recruitment and histone modification at the adult ␤-globin gene in wild-type (WT)/locus control region knockout (⌬LCR) heterozygous mice and in murine erythroleukemia (MEL) cells. Although histone acetylation and methylation (Lys 4) are high before and after MEL differentiation, recruitment of the erythroid-specific activator NF-E2 to the promoter and preinitiation complex (PIC) assembly occur only after differentiation. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
166
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(186 citation statements)
references
References 54 publications
(85 reference statements)
15
166
1
1
Order By: Relevance
“…5C and data not shown). In addition, as shown (18,22,28), p45 recruitment to the LCR and ␤-globin promoter is not detectable in uninduced cells and peaks 4-5 days after DMSO treatment. These results indicate that the hememediated departure of Bach1 from the LCR is not sufficient for the activation of ␤-globin expression or the induction of MEL cell differentiation.…”
Section: Competitive Binding Of Bach1 and Nrf2mentioning
confidence: 78%
See 1 more Smart Citation
“…5C and data not shown). In addition, as shown (18,22,28), p45 recruitment to the LCR and ␤-globin promoter is not detectable in uninduced cells and peaks 4-5 days after DMSO treatment. These results indicate that the hememediated departure of Bach1 from the LCR is not sufficient for the activation of ␤-globin expression or the induction of MEL cell differentiation.…”
Section: Competitive Binding Of Bach1 and Nrf2mentioning
confidence: 78%
“…Gene expression can be regulated by recruitment of RNA polymerase II (27) and by events downstream of preinitiation complex formation, such as clearance of RNA polymerase from the promoter (28). To gain insight into the pathway of ho-1 gene activation, we performed ChIP assays with an anti-pol II antibody.…”
Section: Competitive Binding Of Bach1 and Nrf2mentioning
confidence: 99%
“…Indeed, DNA looping and interactions of distal enhancers and locus control regions with promoters are important for the expression of MHC class II and ␤-globin genes (12,42), which are regulated at the level of transcriptional elongation. Moreover, one study found AIRE to be associated with such matrix attachment sites (44).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that the primary role of the LCR is to enhance the transition from transcription initiation to elongation (9). However, the LCR does not provide the temporal specificity of globin gene expression as transgenic mice lacking this region still exhibit appropriate developmental switching (10).…”
mentioning
confidence: 99%